2017
DOI: 10.1016/j.jpain.2016.10.021
|View full text |Cite
|
Sign up to set email alerts
|

Severe Pain in Veterans: The Effect of Age and Sex, and Comparisons With the General Population

Abstract: This study provides national prevalence estimates of US military Veterans with severe pain, and compares Veterans to nonveterans of similar age and sex. Data used are from the 2010–2014 National Health Interview Survey (NHIS) on 67,696 adults who completed the Adult Functioning and Disability (AFD) Supplement. Participants with severe pain were identified using a validated pain severity coding system imbedded in the NHIS AFD. It was estimated that 65.5% of US military Veterans reported pain in the previous 3 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
139
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 208 publications
(144 citation statements)
references
References 37 publications
4
139
0
1
Order By: Relevance
“…The data are somewhat old; however, more recent studies of the OEF/OIF/OND population have reported similar characteristics. 2 The survey only inquired about a specific set of NPMs, and did not include questions about frequency or dose of medication or NPM treatment. Moreover, although questions were worded to inquire specifically about treatments used for pain, it is possible that some participants endorsed NPM use when that NPM was not pain-focused (e.g., attended psychotherapy that was not pain-focused), and it is not possible to examine details regarding NPMs (e.g., if therapy provided was an evidence-based intervention).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The data are somewhat old; however, more recent studies of the OEF/OIF/OND population have reported similar characteristics. 2 The survey only inquired about a specific set of NPMs, and did not include questions about frequency or dose of medication or NPM treatment. Moreover, although questions were worded to inquire specifically about treatments used for pain, it is possible that some participants endorsed NPM use when that NPM was not pain-focused (e.g., attended psychotherapy that was not pain-focused), and it is not possible to examine details regarding NPMs (e.g., if therapy provided was an evidence-based intervention).…”
Section: Discussionmentioning
confidence: 99%
“…5 Veterans from this era have higher rates of pain than non-veterans of similar ages, than veterans from other eras, and than a representative sample of U.S. adults. 2,[5][6][7][8] Citing efforts to improve pain management and address the opioid crisis, the Department of Veterans Affairs and Department of Defense (VA/DoD) Clinical Practice Guideline, 9 Centers for Disease Control (CDC) Guideline for Prescribing Opioids for Chronic Pain, 10 , and National Pain Strategy (NPS) 11 have highlighted the importance of multimodal treatment for chronic pain including non-opioid pain medication and non-pharmacological modalities (NPMs). The recent VHA State-Of-The-Art (SOTA) Conference, BNon-pharmacological approaches to chronic musculoskeletal pain management,^identified a range of NPMs as having sufficient evidence of effectiveness to encourage their routine availability in VHA.…”
Section: Introductionmentioning
confidence: 99%
“…We did not specifically recruit for participants with CP; the average level of pain disability in our sample was mild to moderate, which was consistent with acute musculoskeletal pain condition samples but lower than CP samples (Anagnostis et al., ). Recent epidemiological studies estimate that up to 65% of U.S. veterans experience CP (Nahin, ); many veterans in our sample are likely to have or be at risk for CP conditions. Finally, this study included primarily male veterans with co‐occurring PTSD and AUD; thus, results may need to be carefully considered for populations outside of this particular subgroup.…”
Section: Discussionmentioning
confidence: 89%
“…; Toblin et al. ; Nahin ). Although recent national initiatives by the VHA have decreased the number of Veterans with opioid prescriptions, there remains concern that patients may be obtaining medications from alternative sources (Gellad et al.…”
mentioning
confidence: 99%
“…This issue is particularly pertinent to the Veterans Health Administration (VHA) as it is the largest integrated health care system in the United States, and Veterans are at increased risk of experiencing chronic pain and developing opioid use disorders (Bohnert et al. ; Nahin ). Chronic pain impacts nearly half of Veterans and almost 25 percent of Veterans received opioid prescriptions as an outpatient in 2012 (Dorflinger et al.…”
mentioning
confidence: 99%